Thematic Progression in Students’ Discussion Essays of Undergraduate English Education Program at Universitas Negeri Padang - Rice Tri Darmila; Hermawati Syarif; Zul Amri (International Journal of Educational Dynamics, 2020)
The aim of this study was to find out how students organize their ideas by seeing the flow of information in the themes and rhemes of clauses in discussion essays. The subject of the study was the sixth semester students of English Department at Universitas Negeri Padang. The total number of sample was 16 students from education program. The sample of the study was collected by using stratified random sampling. The data were collected through students’ writing test of discussion essay. They were asked to write discussion essay at least 4 paragraph in 90 minutes. The result of this study showed that students organized their ideas in three ways of thematic progression, including Simple Linear Progression (SLP), Constant Theme Progression (CTP), and Derived Theme Progression (DTP). However, CTP pattern was predominantly used by students in their essays. Furthermore, it was found that the students’ ability in writing discussion essay seen from thematic progression was still low that they failed to provide development of information and logical arguments in their writing. They tend to organize ideas in different topics in a paragraph that they put new information in the theme position.